RAZÓN, NATURALEZA Y LEY OBSERVACIONES EN TORNO AL FUNDAMENTO CLÁSICO DE LA LEY NATURAL EN TOMÁS DE AQUINO. - Doyle Sánchez, Daniel (Revista Española de Filosofía Medieval, 2025)
This article examines the foundations of natural law within the classical tradition, with particular attention to the reception of Cicero’s thought and its development in the Thomistic synthesis. It analyzes how Cicero weaves together Stoic, Platonic, and Aristotelian elements to formulate a rational, immutable, and universal norm -the lex naturae-which links the human and the divine. The study then turns to the transformation carried out by Thomas Aquinas, who conceives natural law as the active participation of human reason in the eternal law, while preserving its theological grounding. The paper seeks to reclaim the concept of nature within ethical discourse and explores the tension between the autonomy of practical reason and its orientation toward a transcendent order, proposing a dialogue between the classical tradition and its reintegration into medieval Christian thought.